What's wrong? : personal histories of chronic pain and bad medicine - Williams, Erin (Abrams ComicArts, 2024)
What's Wrong? is author, illustrator, and scientific researcher Erin Williams's graphic exploration of how the American health-care system fails us. Focusing on four raw and complex firsthand accounts, plus Williams's own story, this book examines the consequences of living with interconnected illnesses and conditions like: immunodeficiency; cancer; endometriosis; alcoholism; severe depression; PTSD. Western medicine, which intends to cure illness and minimize pain, often causes more loss, abuse, and suffering for those Americans who don't fit within the narrow definition of who the system was built to serve -- cis, white, heterosexual men. The book explores the many ways in which those receiving medical care are often overlooked, unseen, and doubted by the very clinicians who are supposed to heal them. What's Wrong? is also a beautiful celebration of nontraditional modes of healing, of how we become whole not because of health care but despite it.